Semion wave function and energetics in a chiral spin liquid on the Kagome lattice - Cincio, L.; Vidal, G.; Bauer, Bela (arXiv preprint arXiv:1506.03351, 2015)
Recent years have seen the discovery of a chiral spin liquid state – a bosonic analogue of a fractional Quantum Hall state first put forward by Kalmeyer and Laughlin in 1987 – in several deformations of the Heisenberg model on the Kagome lattice. Here, we apply state-of-the-art numerical techniques to one such model, where breaking of the time-reversal symmetry drives the system into the chiral phase. Our methods allow us to obtain explicit matrix-product state representations of the low-lying excitations of the chiral spin liquid state, including the topologically non-trivial semionic excitation. We characterize these excitations and study their energetics as the model is tuned towards a topological phase transition.